1988
DOI: 10.1007/bf02284068
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia caused by diffuse idiopathic skeletal hyperostosis

Abstract: Diffuse idiopathic skeletal hyperostosis (DISH) of the spine is often a hazardous radiological finding. Dysphagia, caused by ossification of the anterior longitudinal ligament, may be one of the most important clinical symptoms disturbing the patient. Diagnosis is done by esophagogram, and cervical decompression restores esophageal function. The case of a successfully operated patient is reported and a short overview of the literature is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…the failure to differentiate between back and joint pain and the selection of probands from a department for locomotor diseases) have certainly led to an overestimation of DISH as a cause of back pain. While this study shows that back pain does not occur more frequently in spinal DISH positive probands than in controls, it is well known that spinal DISH may occasionally lead to stenosis of the spinal canal [16][17][18][19] and cause dysphagia [20,21].…”
Section: Discussionmentioning
confidence: 74%
“…the failure to differentiate between back and joint pain and the selection of probands from a department for locomotor diseases) have certainly led to an overestimation of DISH as a cause of back pain. While this study shows that back pain does not occur more frequently in spinal DISH positive probands than in controls, it is well known that spinal DISH may occasionally lead to stenosis of the spinal canal [16][17][18][19] and cause dysphagia [20,21].…”
Section: Discussionmentioning
confidence: 74%
“…Fahrer and Markwalder reported that dysphagia was a frequent symptom in 20% of DISH patients, and that the C5/6 vertebral level was involved in up to 75% of these cases [5]. The main cause of this symptom is related to anatomical characteristics of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical involvement in DISH can be either asymptomatic or associated with various symptoms, including dysphagia, dyspnea, dysphonia, foreign body sensation, hoarseness, stridor, spinal rigidity, cervical pain, and neurological signs caused by medullary compression [ 1 ]. Dysphagia is one of the most common symptoms in patients with DISH, and its prevalence has been reported to be 17–25% in patients with DISH affecting the cervical spine [ 3 , 6 , 7 , 8 ]. In addition to mechanical compression by osteophyte formation, various mechanisms have been proposed to result in DISH-related dysphagia, including local inflammation, osteophyte-induced muscle spasm, restriction of movement of the epiglottis and larynx, and retention of food in the pyriform sinus due to indentation of the pharynx.…”
Section: Introductionmentioning
confidence: 99%